Magnesium-related gene ITGAL: a key immunotherapy predictor and prognostic biomarker in pan-cancer - Lin, Fengjie; Yang, Hanxuan; Huang, Zongwei; Li, Ying; Ding, Qin; Ye, Yunbin; Qiu, Sufang (Frontiers in Pharmacology, 2024)
Background: Integrin subunit alpha L (ITGAL) is crucial for activating CD8+ T cells through magnesium-mediated immune synapse formation and specific cytotoxicity. ITGAL might exert an important function in the growth and transformation of cancer. Methods: Our study comprehensively analyzed ITGAL expression across various cancers, validated by Immunochemistry (IHC) in the laboratory. ITGAL showed prognostic significance in pan-cancer patients, correlated with clinical features, and associated with specific signaling pathways. We also observed a relationship between ITGAL and immune cell infiltration. In HNSCC, ITGAL demonstrated prognostic value and potential implications for immunotherapy response and novel drug targets. Results: ITGAL expression linked to tumor prognosis across 27 cancers. Elevated ITGAL correlated with good prognosis in CESC, LUAD, SARC, HNSCC, and SKCM. ITGAL involved in immune regulation pathways and showed positive correlation with immune cell infiltration. ITGAL associated with CD8+ T cell infiltration. And high ITGAL expression in CD8+ T cells and NK cells. In HNSCC, ITGAL linked to favorable prognosis and sensitivity to immunotherapy. Predicted potential drugs for HNSCC. Conclusion: ITGAL is remarkably associated with CD8+T cells and crucial in the tumor immune microenvironment of pan-cancer. Furthermore, our findings may provide a targeted anti-tumor strategy for ITGAL by influencing the tumor immune microenvironment.